2016
DOI: 10.1620/tjem.240.227
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between Ideal and Actual Fasting Duration in the Treatment of Patients with Aspiration Pneumonia: A Nationwide Survey of Clinicians in Japan

Abstract: In Japan, aspiration pneumonia is common among the elderly and patients are often treated by temporary discontinuation of meals. However, there are few published studies on the fasting duration for aspiration pneumonia treatment. Therefore, we conducted the present study to assess the opinions of clinicians regarding the fasting duration for the treatment of patients with aspiration pneumonia and the actual medical practice with regard to oral ingestion in hospitalized patients with aspiration pneumonia. We ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Returning the administered questionnaire was considered as consent to participate by the participants. Details regarding fasting duration and resumption of oral intake following aspiration pneumonia have been published previously …”
Section: Methodsmentioning
confidence: 99%
“…Returning the administered questionnaire was considered as consent to participate by the participants. Details regarding fasting duration and resumption of oral intake following aspiration pneumonia have been published previously …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, our research has shown that 89.4% of medical institutions implemented short‐term fasting while treating patients with aspiration pneumonia . However, the resumption of oral intake is critical to the quality of life and likelihood of recurrence among patients with aspiration pneumonia .…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, our research has shown that 89.4% of medical institutions implemented short-term fasting while treating patients with aspiration pneumonia. 11 However, the resumption of oral intake is critical to the quality of life and likelihood of recurrence among patients with aspiration pneumonia. 3 Nevertheless, the factors that are used to determine the timing of oral intake resumption have not been discussed, and this timing is typically based on the attending clinician's judgment and experience.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in Japan the average response rate is 21.3% in mail-in and unpaid surveys without reminder like the present study (Hagihara et al 2006), and that might give a hint to the reason for the low response rate in physicians. On the other hand, there is a report that the response rate was less than 15% (Kenzaka et al 2016) and, therefore, the response rate of the present study is considered to represent physicians above a certain level.…”
Section: Study Limitationsmentioning
confidence: 67%